Weltbeschreibung – Weltbild – Weltanschauung. Annäherung an einige Begriffe - Sperling, Walter (Zeitschrift für Geographiedidaktik (ZGD), 2004)
Jan Amos Comenius (č Komenský), 1592-1670, was one of the most celebrated educational reformers of early modern times. He was not only a famous educationalist, but also a theologian, a cosmograph and a scientist. In this paper some ideas about the world-view of Comenius are going to be discussed by the interpretation of some emblematic figures. The Christian view of the world is determined by the creation story (the book of Genesis) in the Holy Bible. European world-views of the early 17th century were influenced by religious, social and economic changes which had taken place after the reformation and counter-reformation. The imagination of World and Universe also changed radically. The globe became a symbol of the world and the beneficial role of God. In some of his early papers and also in the famous "Orbis pictus" (The Visible World), 1658, Comenius gave a clear picture of the Creation of the world, the lithosphere, the hydrosphere, the atmosphere, the biosphere and the origins of mankind. In his later manuscripts he puts emphasis on the geocentric system and developed a "Lexicon Reale Pansophicum", which is part of "De rerum humanarum emendatione consultation catholica", which was not printed until 1966. Contemporary researchers, first of all Ferdinand Seibt (1927-2003) stated that Comenius had been one of the most influential utopists.